Communication About End of Life for Patients Living With Amyotrophic Lateral Sclerosis: A Scoping Review of the Empirical Evidence - Genuis, Shelagh K.; Luth, Westerly; Campbell, Sandra; Bubela, Tania; Johnston, Wendy S. (Frontiers in Neurology, 2021)
Background: Communication about end of life, including advance care planning, life-sustaining therapies, palliative care, and end-of-life options, is critical for the clinical management of amyotrophic lateral sclerosis patients. The empirical evidence base for this communication has not been systematically examined. Objective: To support evidence-based communication guidance by (1) analyzing the scope and nature of research on health communication about end of life for amyotrophic lateral sclerosis; and (2) summarizing resultant recommendations. Methods: A scoping review of empirical literature was conducted following recommended practices. Fifteen health-related and three legal databases were searched; 296 articles were screened for inclusion/exclusion criteria; and quantitative data extraction and analysis was conducted on 211 articles with qualitative analysis on a subset of 110 articles that focused primarily on health communication. Analyses summarized article characteristics, themes, and recommendations. Results: Analysis indicated a multidisciplinary but limited evidence base. Most reviewed articles addressed end-of-life communication as a peripheral focus of investigation. Generic communication skills are important; however, substantive and sufficient disease-related information, including symptom management and assistive devices, is critical to discussions about end of life. Few articles discussed communication about specific end-of-life options. Communication recommendations in analyzed articles draw attention to communication processes, style and content but lack the systematized guidance needed for clinical practice. Conclusions: This review of primary research articles highlights the limited evidence-base and consequent need for systematic, empirical investigation to inform effective communication about end of life for those with amyotrophic lateral sclerosis. This will provide a foundation for actionable, evidence-based communication guidelines about end of life. Implications for research, policy, and practice are discussed.